Decision reinvestment, pattern recall and decision making in rugby union. (July 2019) - Sherwood, Sebastian M.; Smith, Tiaki B.; Masters, Rich S.W.
Abstract: The ability to recognise patterns of play and then respond rapidly and appropriately under pressure is considered fundamental for successful performance in rugby. Decision reinvestment, a predisposition to consciously process decision-making, has been shown to negatively affect performance under pressure and may play a role in pattern recognition. Study 1 assessed the role of decision reinvestment in pattern recall speed and accuracy. Professional rugby players (N = 57) viewed still images of structured rugby scenarios for 5 s before occlusion. Participants then recalled the positions of six specified players from each scenario as quickly and as accurately as possible on a blank template. Propensity for conscious processing of decision-making was assessed using the Decision Specific Reinvestment Scale, and examined with respect to recall accuracy and decision time. Results suggested that higher scores were associated with slower recall speed and poorer accuracy. Study 2 tested whether the findings in Study 1 were due to memory decay associated with slower decision processes. Skilled rugby players (N = 41) completed the same procedure as Study 1; however, following occlusion they either recalled the six players in any order (Whole Report) or recalled one half of the players (specified) before the other half (Constrained Report). Recall of the second half of the players was found to be significantly less accurate than the first half, in both the Whole and Constrained Report conditions. This suggests that increased time between encoding and retrieval of visual information leads to a decay in memory of players' positioning. Highlights: High decision reinvestors are slower at recalling patterns. High decision reinvestors are also less accurate at recalling patterns. Decay theory is one explanation for reduced accuracy as recall time increases. Coaches should promote quicker, pattern dependent decision making.